2021
DOI: 10.1177/17085381211002728
|View full text |Cite
|
Sign up to set email alerts
|

High inter- and intra-observer agreement for measuring tissue oxygenation of the plantar surface of the foot in healthy participants with the Hyperview®: A pilot study

Abstract: Objectives The Hyperview® is a novel camera that applies hyperspectral imaging to project local concentrations of oxyhaemoglobin (OXY), deoxyhaemoglobin (DEOXY) and O2-saturation (O2-SAT) in a map. In this pilot validation study, we assessed inter - and intra-observer agreement for measuring OXY, DEOXY and O2-SAT in healthy participants. Methods The plantar region of the right foot was assessed with the Hyperview® in 50 healthy participants. Two consecutive pictures were taken by the same observer, followed by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Published studies reporting on average values of Hyperview ® measurements in healthy participants show a wide variation. 8,16 Kleiss et al 8 found an average for OXY of 85.2 arbitrary units (SD 24.9) whereas van Schilt et al 10 reported an average of 69.6 (SD 21.8). Therefore, we advice to perform pre-intervention measurements to compare the patient with his or her own measurements to observe changes.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Published studies reporting on average values of Hyperview ® measurements in healthy participants show a wide variation. 8,16 Kleiss et al 8 found an average for OXY of 85.2 arbitrary units (SD 24.9) whereas van Schilt et al 10 reported an average of 69.6 (SD 21.8). Therefore, we advice to perform pre-intervention measurements to compare the patient with his or her own measurements to observe changes.…”
Section: Discussionmentioning
confidence: 99%
“…13 Within the same session a Hyperview ® measurement was performed according to a standardized protocol, which has been validated in healthy participants in a previous study. 10 In this protocol, the room temperature was set at an ambient temperature of 20-23°of Celsius. The patients were placed in a supine position on an examination table with the head of the table elevated to 45°.…”
Section: Abi Toe Pressure and Hyperview ® Measurementsmentioning
confidence: 99%
See 3 more Smart Citations